Pengenalan Wajah Secara Real Time Menggunakan Metode Camshift dan Operator Erosi Berdasarkan Citra Wajah - Sultoni Sultoni; Rudy Hariyanto (JICTE (Journal of Information and Computer Technology Education), 2017)
Facial recognition is a research topic that is quite a lot done by researchers in recent decades, because many benefits in this study such as security system and survelliance. This research is a development or modification of previous research. Where previous research used camhshift method for detection and tracking, in this research is by performing erosion operators on the detection and tracking process using camshift. Based on the results of the test produced a fairly good accuracy and with a fairly fast computation time. So that the future can be applied to enter attendance attendance system or to masku secret room by doing engineering such as merging with microcontroller and so on, so the benefits can be more felt.